Transport of β-Galactosides in Lactobacillus plantarum NC2 - Jeffrey, Scott R. (1990)
The ability of Lactobacillus plantarum NC2 to transport thiomethyl-β-d-galactoside in the presence or absence of various inhibitors was investigated to determine the mechanism of β-galactoside transport in this bacterium. A novel system employing l-arabinose as an energy-generating compound is described, and evidence that this transport is energized by an ATP-driven proton motive force is presented.